COMMUNICATION MODULES FOR DATA TRANSMISSION IN PHOTOVOLTAIC PERFORMANCE MONITORING AND ANALYSIS SYSTEMS : COMMUNICATION MODULES FOR DATA TRANSMISSION IN PHOTOVOLTAIC PERFORMANCE MONITORING AND ANALYSIS SYSTEMS - Ivanova, Iliyana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
The paper discusses the wireless communication modules used for monitoring photovoltaic systems-ZigBee, Wi-Fi, Bluetooth, GSM and LoRa. The aim is to compare the main features, advantages and disadvantages of each of these technologies. The analysis identifies the need for reliability, low power consumption and secure data transmission in the design of the systems.